Sustainability in corn production management: A multi-objective approach - Supalin Tiammee (2020)
© 2020 Elsevier Ltd Improper disposal of agricultural wastes, especially by open burning in the fields, generates enormous amounts of greenhouse gases (GHGs), Polycyclic Aromatic Hydrocarbons (PAHs) and Particulate Matters (PM). This study uses multi-objective optimization to analyze the environmental and economic impacts of agricultural production management. The focus is on the sustainability of corn production management encompassing corn-kernel production and management of crop residues. Maximization of economic benefits and minimization of environmental impact are taken into the objective function in order to find trade-offs between them. Comparisons are made between greener disposal methods suggested in the proposed model (organic fertilizer and biomass fuel briquette production) and the common method in use today. The lifetimes of atmospheric CO2 are set to be 1, 5, 25, 50, 100 and 200 yrs. The weighted sum approach is applied to solve the proposed model. The case study illustrating the model involves a regional economic and tourism hub recently plagued by haze problems from open burning of crop residues. With results in all cases showing that adding proper waste disposals leads to total profit reduction of only 0.35–1.96%, this study shows that the correct disposal method can greatly reduce environmental problems while only slightly affecting total profit from production.